Information System for Course Quotas Forecasting using Trend Analysis Method - Afwan Anggara; Widya Setiafindari (Institut Teknologi Dirgantara Adisutjipto, 2023)
Determining the class quota at each period of filling out the KRS (Study Plan Card) at the beginning of the semester is often an activity that cannot be determined easily. It is due to several important factors in it, one of the most influential and difficult things is the uncertainty when determining the quota for the number of students who will take the course, if later there is an error in predicting the number of students who will take the course, then the class quota that is prepared will certainly be less so that it leads to the disruption of the ongoing Student KRS registration process. The method used in this study is predicting using trend analysis which aims to determine how much capacity or inventory is needed for decision-making, then a system will be designed that can be used to predict the number of predicting quotas for courses that will be provided. The system design applies the system development method with UML. The stages of the process are carried out from collecting and processing subject offer quota data several previous academic years. This research has succeeded in building a model to make predictions using the Trend Analysis method, so that it can be used as a recommendation for the number of quotas offered for the next academic year.